Deformation Mode and Energy Absorption Analysis of Bi-Tubular Corrugated Crash Box Structure - Choirotin, Ismi; Choiron, Moch. Agus; Purnowidodo, Anindito; Darmadi, Djarot Bangun (International Journal of Integrated Engineering, 2021)
In this research, the characteristic of crash box with bi-tubular corrugated structure are numerically examined under axial loading condition. The crash box characteristic were observed in the compression test of aluminum alloy (AA6061) using ANSYS software. The comparation were carried out on two geometrical types, namely: ordinary corrugated tube (OCT) and bi-tubular corrugated tube (BCT). The result showed that comparing both of crash box structure exhibit the Simultaneous crush mode (S-mode) deformation. The force-displacement present a stable diagram without any fluctuation. BCT structure resulted 71% energy absorption capacity increment compared to OCT structure. The highest energy absorbed by BCT structure was 10.8 kJ. There are no significant specific energy absorption different between the specimen and the highest SEA occur at OCT structure with 31.281 kJ kg-1.